2000
DOI: 10.1002/1096-8652(200010)65:2<119::aid-ajh5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the G1691A mutation in the factor V gene (factor V Leiden) and the G20210A prothrombin gene mutation in the Thai population

Abstract: We investigated the prevalence of a genetic variation in the factor V gene (G1691A Leiden mutation) and the prothrombin gene (G20210A) using polymerase chain reaction techniques in samples from 500 normal Thai population and among 50 unselected Thai patients with an objectively confirmed history of deep venous thrombosis. The prevalence of factor V Leiden and the prothrombin G20210A gene mutation in a group of 500 healthy controls was 0.2% in both groups (allele frequency of 0.1%). Of the 50 adult patients stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…The cause of the lower incidence of VTE in the Taiwanese population remains unclear, but may be partly attributed to a lower incidence of primary hypercoagulable disease predisposing to VTE. Previous studies have shown a lower incidence of FV Leiden mutation in Asian populations (0.5%) than in Caucasians (5%) [20][21][22]. In addition, Steffen et al [23] reported that a diet including abundant vegetables, fish and little meat was associated with lower risk of incident VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of the lower incidence of VTE in the Taiwanese population remains unclear, but may be partly attributed to a lower incidence of primary hypercoagulable disease predisposing to VTE. Previous studies have shown a lower incidence of FV Leiden mutation in Asian populations (0.5%) than in Caucasians (5%) [20][21][22]. In addition, Steffen et al [23] reported that a diet including abundant vegetables, fish and little meat was associated with lower risk of incident VTE.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The Australian population includes many ethnic groups among them the Asian population, Caucasian and Middle East, are those who had shown a frequency of 0.3%, 2.8% and 6.2%, respectively. 22 On the other hand, Asian population presented a lower prevalence of this polymorphism than Thai people with 0.5% 22 and Japanese, Chinese, Korean and Mongolian whose prevalence is closed to 0%. 3 It is interesting to observe that the prevalence of FV Leiden between the healthy population of a region in Turkey is 8.7% of which 1% presents homozygosity 24 and a Lebanese community showed a frequency of 13.8%.…”
Section: Discussionmentioning
confidence: 99%
“…16 The relatively low incidence of VTE in Asians and Hispanics has not been explained, but may relate to a lower prevalence of genetic factors predisposing to VTE, such as factor V Leiden in Asian populations (0.5%) compared with Caucasians (5%). [17][18][19] In venographic studies of patients recovering from hip replacement surgery, the incidence of asymptomatic VTE in Asians appears comparable with that in North America, 20 -22 suggesting that the difference in VTE incidence may be related to less efficient inactivation of coagulation by activated protein C or less fibrinolytic activity among Caucasians. The lower incidence of VTE in Hispanics than in African Americans cannot be explained by a lower prevalence of factor V Leiden, as this genetic condition is present in Ϸ2% of Hispanic and Ͻ1% of African Americans.…”
Section: Effect Of Race/ethnicitymentioning
confidence: 98%